2018
DOI: 10.1039/c8bm00928g
|View full text |Cite
|
Sign up to set email alerts
|

A potent, minimally invasive and simple strategy of enhancing intracellular targeted delivery of Tat peptide-conjugated quantum dots: organic solvent-based permeation enhancer

Abstract: Organic solvent in low percentage offers a great way to enhance vesicle escape and intracellular targeted delivery of nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Exosomes, 40–150 nm extracellular vesicles (EVs) released by cells, have emerged as a novel endogenous delivery system [1821]. As natural carriers that transfer bioactive molecules between cells, exosomes present several features, including low immunogenicity, biodegradability, ability to encapsulate endogenous bioactive molecules, and the ability to cross the BBB [22–24]. In previous work, to improve the targeting characteristics of exosomes, we developed a rapid and efficient method to conjugate functional ligands onto exosomal surfaces using bio-orthogonal copper-free azide alkyne cyclo-addition (click chemistry) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, 40–150 nm extracellular vesicles (EVs) released by cells, have emerged as a novel endogenous delivery system [1821]. As natural carriers that transfer bioactive molecules between cells, exosomes present several features, including low immunogenicity, biodegradability, ability to encapsulate endogenous bioactive molecules, and the ability to cross the BBB [22–24]. In previous work, to improve the targeting characteristics of exosomes, we developed a rapid and efficient method to conjugate functional ligands onto exosomal surfaces using bio-orthogonal copper-free azide alkyne cyclo-addition (click chemistry) [25].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the results demonstrated that smart nano delivery efficiently accumulated in tumour sites and induced apoptosis in treated cells [100]. Moreover, Yong et al investigated the use of permeation enhancers based on organic solvents [101]. They demonstrated that the addition of organic solvents, such as dimethyl sulfoxide, to the aqueous nanomaterial solution can enhance intracellular vesicle escape without compromising membrane integrity.…”
Section: Cell-penetrating Peptide Conjugation With Nanoparticles Fmentioning
confidence: 97%
“…They demonstrated that the addition of organic solvents, such as dimethyl sulfoxide, to the aqueous nanomaterial solution can enhance intracellular vesicle escape without compromising membrane integrity. Through conjugation of QD NP with CPP and organic solvent, the authors observed a significant enhancement in translocation across cell membranes [101].…”
Section: Cell-penetrating Peptide Conjugation With Nanoparticles Fmentioning
confidence: 99%
“…After conjugation with CPPs, the cellular internalization of NPs can be enhanced significantly. In particular, the peptides containing special lysine (K)-, arginine (R)-, or proline (P)-rich motifs (known as nuclear localization sequences (NLSs)) can efficiently transport NPs into the nucleus [ 133 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. As early as 1999, Josephson and colleagues found that Tat peptide modified SPIOs were internalized into lymphocytes over 100-fold more efficiently than nonmodified NPs [ 138 ].…”
Section: Employing Peptide Functionalized Nanoparticle As Positive Tumor-targeting Nanomedicinesmentioning
confidence: 99%